A Comprehensive Review of Plant Volatile Terpenoids, Elucidating Interactions with Surroundings, Systematic Synthesis, Regulation, and Targeted Engineering Production - Wei Jin; Zhongzhou Yang; Kedong Xu; Qiuping Liu; Qi Luo; Lili Li; Xiaohong Xiang (Biology)
Plants require a flexible avoidance mechanism as they need to cope with external stimuli and challenges through complex specialized metabolites, among which volatile terpenoids make outstanding contributions, acting as key media signal substances in the cooperation between plants and surrounding organisms. In recent decades, the research on the identification and functional characterization of terpenoid synthase and factors regulating metabolic shunts has gained significant attention, leading to substantial progress and notable achievements. However, with the popularization of terpenoids in insect and disease prevention, medical care, cosmetics, and other fields, coupled with increasing resistance to artificially produced chemical products, the demand for natural terpenoids has outpaced supply, prompting the emergence and popularity of targeted engineering for the mass production of terpenoids using microorganisms and plants as platforms. In this paper, we provide a detailed overview of the key knowledge and research progress of volatile terpenoids with regard to multiple functions, complex synthetic pathways, key terpenoid synthase genes, related regulatory factors, and target engineering.